Trends of intraseasonal descriptors of wet and dry spells over equatorial eastern Africa. - (:unkn) unknown (My University, 2018)
Many African countries whose economies are largely based on weather/climate sensitive sectors are vulnerable to long‐term changes in weather and climate. This study is aimed at assessing whether the recent decades have observed any significant trend in the intraseasonal descriptors (ISDs) of wet and dry spells at local and sub‐regional levels at seasonal and monthly timescales over equatorial eastern Africa (EEA). Daily rainfall observations over 36 stations and spanning a period of 51 years (1962–2012) were used.The study has expanded on previous results that showed contrasting trends on seasonal totals between the two rainfall seasons by demonstrating that this also affects the ISDs. At the local level, it was observed that during the long rainfall season, a given ISD would have a significant trend over several neighbouring locations, which was not the case during the short rainfall season. Secondly, for the short rainfall season, a given location would have significant trend in several ISDs. Finally, when a given ISD had a significant trend at seasonal timescale during the long rainfall season, the same ISD would have significant trends in the second and third months of the season and rarely in the first month. Such a feature was not observed for the short rainfall season. Binomial probability distribution assessment confirmed that the significant trends in the various ISDs during the long rainfall season did not occur by mere chance.
Keywords: African Research